2008
DOI: 10.1371/journal.pone.0003740
|View full text |Cite
|
Sign up to set email alerts
|

Integrative MicroRNA and Proteomic Approaches Identify Novel Osteoarthritis Genes and Their Collaborative Metabolic and Inflammatory Networks

Abstract: BackgroundOsteoarthritis is a multifactorial disease characterized by destruction of the articular cartilage due to genetic, mechanical and environmental components affecting more than 100 million individuals all over the world. Despite the high prevalence of the disease, the absence of large-scale molecular studies limits our ability to understand the molecular pathobiology of osteoathritis and identify targets for drug development.Methodology/Principal FindingsIn this study we integrated genetic, bioinformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
443
6
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 462 publications
(478 citation statements)
references
References 39 publications
17
443
6
12
Order By: Relevance
“…Over the past decade, mounting evidence shows that a variety of miRNAs was involved in the occurrence and development of OA. It was identified that the expression of miR‐483, miR‐22, miR‐377, miR‐103, miR‐16, miR‐223, miR‐30b, miR‐23b and miR‐509 was up‐regulated in osteoarthritic cartilage of human knee join compared to normal cartilage, but the expression of miR‐29a, miR‐140, miR‐25, miR‐337, miR‐210, miR‐26a and miR‐373 was down‐regulated 22. Dimitrios Iliopoulos et al .…”
Section: Discussionmentioning
confidence: 96%
“…Over the past decade, mounting evidence shows that a variety of miRNAs was involved in the occurrence and development of OA. It was identified that the expression of miR‐483, miR‐22, miR‐377, miR‐103, miR‐16, miR‐223, miR‐30b, miR‐23b and miR‐509 was up‐regulated in osteoarthritic cartilage of human knee join compared to normal cartilage, but the expression of miR‐29a, miR‐140, miR‐25, miR‐337, miR‐210, miR‐26a and miR‐373 was down‐regulated 22. Dimitrios Iliopoulos et al .…”
Section: Discussionmentioning
confidence: 96%
“…miRNAs have been reported to master-regulate diverse physiologic cellular functions including differentiation, apoptosis, (55) oxidative stress, (56) and remodeling. (57) Altered miRNA serum profiles were also described for many pathologic processes, including diverse types of cancer, (58,59) and chronic diseases such as osteoarthritis, (60,61) coronary heart disease, (62) and T2D. (22) However, to our knowledge this is the first study that has investigated the expression profiles of serum miRNAs in T2D postmenopausal women with respect to their history of fragility fractures.…”
Section: Discussionmentioning
confidence: 99%
“…The role of let-7f in tumorigenesis and metastasis is well known (O'Day and Lal, 2010); therefore, we did not place much emphasis on this miRNA. However, miR-22 is a relatively new player and has been linked to cellular metabolism and chronic inflammatory diseases such as osteoarthritis (Iliopoulos et al, 2008). Normal mammary stem cells express high levels of miR-22 and little-to-no let-7; however, during progressive differentiation, the expression of miR-22 decreases and expression of let-7 family members is induced (Ibarra et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, it appears that the role of miR-22 is different in a metastasis setting. miR-22 targets the extracellular environment via matrix metalloproteinases and interleukins and thus has a function in inflammatory conditions (Iliopoulos et al, 2008). Putative downstream targets of miR-22 include ERBB3, CDC25C, EVI-1, SIRT1, AKT3, SATB2, HDAC4, CBL, peroxisome proliferator activated receptor a and BMP7.…”
Section: Discussionmentioning
confidence: 99%